2021
DOI: 10.3389/fimmu.2021.639174
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Host Serum Protein Biomarkers of Tuberculosis in sub-Saharan Africa

Abstract: Accurate and affordable point-of-care diagnostics for tuberculosis (TB) are needed. Host serum protein signatures have been derived for use in primary care settings, however validation of these in secondary care settings is lacking. We evaluated serum protein biomarkers discovered in primary care cohorts from Africa reapplied to patients from secondary care. In this nested case-control study, concentrations of 22 proteins were quantified in sera from 292 patients from Malawi and South Africa who presented pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Meanwhile, immunodiagnostics has received considerable attention as an alternative for discrimination of MTB infection status in recent years (63)(64)(65)(66)(67)(68)(69)(70). Nevertheless, the identified biomarkers including proteins and cytokines in serum or plasma for diagnostic aim may not be specific for TB due to the influence brought by other immune related diseases such as infection and autoimmune diseases (71)(72)(73)(74)(75)(76)(77). Thus, an intensified search for suitable host-specific biomarkers targeting TB diagnostic purpose was urgently needed (78).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, immunodiagnostics has received considerable attention as an alternative for discrimination of MTB infection status in recent years (63)(64)(65)(66)(67)(68)(69)(70). Nevertheless, the identified biomarkers including proteins and cytokines in serum or plasma for diagnostic aim may not be specific for TB due to the influence brought by other immune related diseases such as infection and autoimmune diseases (71)(72)(73)(74)(75)(76)(77). Thus, an intensified search for suitable host-specific biomarkers targeting TB diagnostic purpose was urgently needed (78).…”
Section: Discussionmentioning
confidence: 99%
“…Activity measurement of the enzyme adenosine deaminase (ADA) and its two isoforms (ADA1 and ADA2) in a variety of biological fluids has been suggested to aid in the diagnosis of ATB; however, ADA activity in serum has never been used to distinguish ATB from LTBI (19)(20)(21)(22)(23). Several studies exploring the use of inflammatory serum cytokines involved in Mtb infection have been performed (24)(25)(26)(27)(28)(29), with inconsistent conclusions for cytokine production in Mtb-specific stimulated CD4 + and CD8 + T cells (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Most of these studies showed that the discriminative value of a single marker is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Active TB predictive biosignatures included; “IL-6, MIP-1β, VEGF and saliva G-CSF and MIP-1α” ( 60 ) in a Ugandan population. In a South African study, the predictive biosignature among the HIV co-infected patients included IFN-gamma, fibrinogen, IFN- alpha-2, MMP-2 ( 61 ), and IL-1RA; ApoA-1, CFH, CRP, IFN-g, IP-10, SAA, and transthyretin ( 62 ).…”
Section: Resultsmentioning
confidence: 99%